Pengaruh Kedisiplinan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Agro Boga Utama Jakarta Selatan - Mashudi, Arief Tri (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
Performance is a description of a result that can be measured by the effectivenessand efficiency of a job carried out by human resources in realizing the goals,objectives, vision, and mission that are realized through a company's planningstrategy. This study aims to determine and analyze the influence of the environmentand motivation on employee performance at PT Agro Boga Utama. This study uses aquantitative statistical approach method. The sampling technique used is saturatedsampling which has 38 respondents. The data collection technique uses observationthrough questionnaires. The results of this study indicate that work discipline (X1)has a significant effect with a value of 0.706 or 70.6%, which means that the workdiscipline variable (X1) has a strong influence on employee performance (Y). workmotivation (X2) has a significant effect with a value of 0.666 or 66.6%, which meansthat the discipline variable (X1) has a strong influence on employee performance (Y).work discipline (X1) and work motivation (X2) simultaneously (together) have asignificant influence on employee performance (Y) at PT Agro Boga Utama with avalue of 0.888 or 88.8% influenced by other factors that the researcher did notexamine.